Marine Glycobiology, Glycomics and Lectins - Ozeki, Yasuhiro (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Glycans (carbohydrate chains) of marine creatures are rich and diverse in polysaccharides, glycoproteins, and glycolipids. The chains that are metabolized by glycan-related enzymes (glycosyltransferases and glycosidases) are recognized by glycan-binding proteins (lectins) which regulate cellular processes such as growth, differentiation, and death. Marine glycomics that involves the genome and transcriptome accelerates our understanding of the evolution of glycans, glycan-related enzymes, and lectins. From 2017 to 2019, the Special Issue "Marine Glycobiology, Glycomics and Lectins" of the journal Marine Drugs published scientific articles and reviews, on the background of "glycobiology"-that is, glycan-based biosciences. The aim was to promote the discovery of novel biomolecules that contribute to drug development and clinical studies. This has great potential for establishing connections between the fields of both human health and marine life sciences.This book contains 11 scientific papers representing current topics in comprehensive glycosciences related to therapeutic agents from marine natural products, as outlined.